Molecular Insight Into Key Eco-Physiological Process in Bioremediating and Plant-Growth-Promoting Bacteria - Mandal, Subhrangshu; Saha, Kunal Kumar; Mandal, Narayan Chandra (Frontiers in Agronomy, 2021)
For the past few decades, exercise of massive anthropogenic activity and immense industrialization process, endlessly increase new pollutants to the environment. Effect of such toxic components (heavy metals, pesticides etc.) in our ecosystem vary significantly and are of solemn public health and economic concern. Thereafter, environmental consciousness is growing up amongst consumers and industrialist, and legal constrain on emission, are becoming gradually strict; ultimately resulted to need for cost-effective emission control. Fortunately, certain taxonomically and phylogenetically diverse microorganisms (e.g. sulfur oxidizing/reducing bacteria) are endowed with the capability to remediate such undesired components from diverse habitats along with diverse magnitude of plant growth promoting ability (auxin and siderophore production; phosphate solubilization etc.) by various mechanisms. However, the quirk of fate for pollutant and plant-growth-promoting microbiome research, is even with an early start, genetic knowledge on these systems is still considered to be in its infancy due to unavailability of in-depth functional genomics and population dynamics data from various ecosystems. This knowledge gap can be filled up if we have adequate acquaintance concerning their genetic make-up; so that we can use them in a targeted manner or with considerable operational flexibility in agricultural sector. Amended understanding regarding the genetic basis of potential microbes involved in such processes, has led to the establishment of novel or advanced bioremediation technology (detoxification efficiency of heavy metals); that will apparently polish our understanding in changing view of genomic/genetic landscape in these potential organisms. Our review aimed to unravel the hidden genomic basis and eco-physiological properties of such potent bacteria and their interaction with plant, from various ecosystems.